Primary and Recurrent Focal Segmental Glomerulosclerosis Closely Link to Serum Soluble Urokinase-type Plasminogen Activator Receptor Levels - Jin, J.; Li, Y.W.; He, Q. (Transplantation proceedings, 2015)
Serum soluble urokinase-type plasminogen activator receptor (suPAR) is implicated in the pathogenesis of native and recurrent focal segmental glomerulosclerosis (FSGS). It is elevated in two-thirds of subjects with primary FSGS, but not in people with other glomerular diseases that can differentiate FSGS and other glomerular diseases. We measured the serum soluble urokinase receptor levels and determined their association with clinical and pathologic data in 86 patients with primary FSGS, 5 repeat renal biopsy FSGS, and 6 recurrent FSGS post-transplantation. Healthy controls and patients with minimal change disease and membranous nephropathy were used as controls. The suPAR levels were measured by commercial enzyme-linked immunosorbent assay kits. Patients with primary FSGS (median: 4232, interquartile range 1299–9714 pg/mL) had significantly higher levels of suPAR than those of patients with minimal change disease (median: 2784 pg/mL), membranous nephropathy (median: 3478 pg/mL), and healthy individuals (median: 1994 pg/mL). There was no significant difference in suPAR levels between the 65 patients with minimal change disease and 85 patients with membranous nephropathy. The suPAR levels increased in the 5 repeated renal biopsy FSGS and 6 recurrent FSGS post-transplantation. The suPAR levels were significantly but positively correlated with FSGS, not only primary FSGS but also recurrent FSGS post-transplantation, but negatively correlated with other glomerular diseases. Thus, suPAR levels can differentiate primary FSGS and other glomerular diseases. •The serum soluble urokinase receptor levels are increased in primary and recurrent focal segmental glomerulosclerosis (FSGS).•Allow better risk stratification of patients with FSGS by measuring serum soluble urokinase receptor.•We can distinguish FSGS from other glomerular diseases, especially minimal change disease.